Hands-on XForms simplifying the creation and management of XML formation. - Dubinko, Micah (XML journal :the ultimate enterprise resource.)
Organizations have evolved a variety of systems to deal with the increasing levels of information they must regularly process to remain competitive. Business Process Management (BPM) systems presently take a wide variety of shapes, often including large amounts of ad hoc scripting and one-off implementations of business rules. Such systems tend to be developed incrementally and pose a significant obstacle to continued development and maintenance.